Evaluation of the Short-Term Effect of Bariatric Surgery on the Level of HbA1c - Hadi Salehnia; Abbas Ali Dehghan; Sara Rashki Ghalehnoo (Novelty in Biomedicine)
Background: Obesity is one of the most common diseases in the world, and type 2 diabetes (T2DM) is one of the common complications of obesity. Bariatric surgery is one of the main treatments for the obese. It is recommended that this procedure can improve the status of T2DM, but there is limited data about the short-term effects of bariatric surgery on T2DM status. In this study, we aimed to evaluate the short-term effect of bariatric surgery on the level of HbA1c as a parameter of the status of T2DM during 6 months.